The causal relationship of cigarette smoking to metabolic disease risk and the possible mediating role of gut microbiota - Jingda Zhang; Lin Hou; Shanxiang Lei; Yan Li; Guogang Xu (Ecotoxicology and Environmental Safety)
Background: Cigarette smoking is a leading cause of preventable death worldwide, with its associated diseases and conditions. Emerging evidence suggests that cigarette smoking contributes to a range of pathological metabolic injuries, including diabetes and nonalcoholic fatty liver disease (NAFLD). The impact of gut microbiota on metabolic health and diseases has been observed, but the causality remains uncertain. Objective: To confirm the causal relationship between cigarette smoking and metabolic diseases, and to investigate the possible mediating effect of gut microbiota on these connections. Methods: The relationships among cigarette smoking, metabolic diseases, and the gut microbiome were analyzed by Univariate Mendelian randomization (UVMR). Furthermore, to mitigate the impact of confounding factors, adjusted models were conducted via the multivariate Mendelian randomization (MVMR) method, aiming to improve the accuracy of prediction. Ultimately, the study evaluated the effect of the intermediary factor, gut microbiome, on the relationship between cigarette smoke and metabolic diseases. Results: The phenomenon that a causal relationship between cigarette smoke (249752 individuals) and gut microbiota (7738 individuals), diabetes (406831 individuals), NAFLD (377998 individuals), hypercholesterolaemia (463010 individuals), and obesity (463010 individuals) was observed using UVMR. In the MVMR model, the genetic connection between cigarette smoking, gut microbiota, and type 2 diabetes remained significant. Of note, paraprevotella_clara served an important mediating role in the type 2 diabetes associated with cigarette smoke. Conclusion: This work offered genetic evidence linking cigarette smoke to metabolic diseases, suggesting that the gut microbiota, particularly paraprevotella_clara, might be a crucial mediator in the development of type 2 diabetes caused by cigarette smoke. Our future studies should consider conducting other ethnic groups MR analyses, particularly with larger sample sizes. Still, more in vivo and in vitro work should be carried out to validate the precise effect and molecular mechanisms of the gut microbiome.